Characterisation and modelling of static recovery process of aluminium alloy - Mohd Azizi, Junit (2008)
A comprehensive study of the annealing behavior of aluminum alloy has been carried out in this research. The primary objectives of this work have been to study the effect of recovery on the annealing behavior and to validate the static recovery process of aluminum alloy using Friedel’s model. Annealing is a heat treatment process used to eliminate the residual stresses produced during cold work and static recovery is one of the processes in annealing. This process is the most subtle stage of annealing and no gross microstructure change occurred. In this research, aluminum alloy were to undergo thermo-mechanical process which compression test and annealing process took place. The experimental part has focused on characterisation of the softening reaction. Through this test, the material was tested at different pre-strain which is 2.5%,5%.7.5% and 10% to see the difference stress due to recovery temperature(100oC,150oC,200oC,250oC) and time(1hour,2hour,3hour,4hour). Then, the graph for relationship between degree of recovery,Xrec with temperature, time and pre-strain are plotted. Friedel’s model equation is applied to the experimental result to find the activation energy,Q. For the relationship between degree of recovery,Xrec and temperature, the activation energy,Q is about 732.55 kJ/mol while the activation energy,Q for relationship between degree of recovery,Xrec and time is 224.83 kJ/mol. Finally, the activation energy,Q value from the experimental result are compared with literature review to validate the static recovery process of aluminum alloy using Friedel’s model equation.